Answer:
b(n) = -23 + 18n
Step-by-step explanation:
NOTE - This is an arithmetic sequence, so each number is increasing by addition. If you were in a geometric sequence, however, you'd be multiplying. This means that the explicit formula for the geometric sequence you'll be learning later on will be different.
The formula for explicit formula is b(n)=b(1)+d(n-1). The variable d represents the common difference and the a is whatever number of the term you are using.
Since you have b(1), you look at what your first term is. Plug -5 into a(1).
To find your common difference, find 13-(-5). This is 18, and adding it to the others you can see that it continues.
So, plugging in what you have so far it looks like b(n) = -5 + 18(n - 1)
All we need to do now is simplify.
1. Distribute: -5 + 18n - 18
2. Add like terms: -23 + 18n
Hope this helped and made sense lol.
Answer: 62.
Step-by-step explanation: The mean is the average. In order to find the average, we need to add all of the numbers up, then divide by the number of quizzes. So:
20 + 40 + 40 +40 + 60 + 60 + 60 + 60 + 80 + 80 + 80 + 80 + 100 = 800
800 / 13 = 61.5, appr. 62.
the large bag is 5/6 lb, the smaller bags will be 1/3 lb, so it should be 5/6 ÷ 1/3
![\bf \cfrac{5}{6}\div \cfrac{1}{3}\implies \cfrac{5}{\underset{2}{~~\begin{matrix} 6 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}}\cdot \cfrac{~~\begin{matrix} 3 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}{1}\implies \cfrac{5}{2}\implies 2\frac{1}{2}](https://tex.z-dn.net/?f=%5Cbf%20%5Ccfrac%7B5%7D%7B6%7D%5Cdiv%20%5Ccfrac%7B1%7D%7B3%7D%5Cimplies%20%5Ccfrac%7B5%7D%7B%5Cunderset%7B2%7D%7B~~%5Cbegin%7Bmatrix%7D%206%20%5C%5C%5B-0.7em%5D%5Ccline%7B1-1%7D%5C%5C%5B-5pt%5D%5Cend%7Bmatrix%7D~~%7D%7D%5Ccdot%20%5Ccfrac%7B~~%5Cbegin%7Bmatrix%7D%203%20%5C%5C%5B-0.7em%5D%5Ccline%7B1-1%7D%5C%5C%5B-5pt%5D%5Cend%7Bmatrix%7D~~%7D%7B1%7D%5Cimplies%20%5Ccfrac%7B5%7D%7B2%7D%5Cimplies%202%5Cfrac%7B1%7D%7B2%7D)
Answer: (C) even
<u>Step-by-step explanation:</u>
A function is even when f(x) = f(-x)
A function is odd when f(-x) = -f(x)
f(x) = -2x⁴ + 3x²
f(-x) = -2(-x)⁴ + 3(-x)²
= -2x⁴ + 3x²
f(x) = f(-x) so the function is even
-f(x) = -(-2x⁴ + 3x²)
= 2x⁴ - 3x²
f(-x) ≠ -f(x) so the function is not odd.
You have 5 quarters which equals 25 cents each. Which in total comes to $1.25.
You have 15 dimes which is worth 10 cents each.
Which in total comes to $1.50.
$1.50
+$1.25
=$2.75